Trombose de seios durais. - Luís Costa Matos; Borges Martins; Nuno Canto-Moreira; Ana Gomes; Isabel Martins; Joana Capelo; Pedro Henriques (Acta Médica Portuguesa, 2007)
Dural sinus thrombosis is a rare condition and is often underdiagnosed. Because of its potentially lethal complications, it should always be considered in acute headache differential diagnosis. The authors present a report of two cases, both diagnosed on our department. They make an approach to clinical presentation, diagnosis and treatment of this disease.